2015
DOI: 10.1007/s13147-015-0360-9
|View full text |Cite
|
Sign up to set email alerts
|

Die wirtschaftliche Wirkung der Universitäten im Land Baden-Württemberg

Abstract: Zusammenfassung Die Bewertung der wirtschaftlichen Bedeutung von Universitäten steht zunehmend im politischen Interesse, wenn es um die Rechtfertigung des öffentlichen Mitteleinsatzes für Forschung und Bildung geht. Während regionale Wirkungsanalysen bisher meist auf der lokalen Ebene und für einzelne Einrichtungen durchgeführt wurden, bewertet dieser Beitrag erstmalig den monetären Effekt einer ganzen Hochschullandschaft auf die Wertschöpfung und den Arbeitsmarkt eines großen Flächenlandes in Deutschland. Ein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…This study uses regional multiplier analysis to determine a detailed model of the economic impact of the cultural work of the Mannheim Philharmonic Orchestra and to evaluate it in terms of the subsidies used by the city. The methodological basis for the analysis is a regional economic impact model, which the authors have further developed to assess the regional impact of universities as public research and educational institutions [26,27,[34][35][36].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study uses regional multiplier analysis to determine a detailed model of the economic impact of the cultural work of the Mannheim Philharmonic Orchestra and to evaluate it in terms of the subsidies used by the city. The methodological basis for the analysis is a regional economic impact model, which the authors have further developed to assess the regional impact of universities as public research and educational institutions [26,27,[34][35][36].…”
Section: Methodsmentioning
confidence: 99%
“…The regional multiplier analysis is used to model the periodic economic effect of the expenditures associated with a facility on increasing demand, value-added, income, and jobs and tax revenues. The total effect is the sum of three individual effects [34]:…”
Section: Methodsmentioning
confidence: 99%
“…Universities fulfil a wide range of roles: ◆ Generating knowledge ◆ Providing qualifications for skilled workers ◆ Establishing know-how transfer between companies and universities ◆ Creating regional knowledge infrastructures ◆ Developing technical innovations, in the form of patents or spin-offs ◆ Participating in political and civil decision-making processes ◆ Providing intellectual, cultural, artistic, or moral impulses ◆ Increasing the autonomous demand by the regional expenditures of the universities for material and services (Glückler-Panitz-Wuttke 2015).…”
Section: The Role and The Relevance Of Universitiesmentioning
confidence: 99%
“…Input-output related income and employment multipliers (or a combination of both kinds of multipliers) are only applied by Blume and Fromm (2000), Wenke (2002), Spehl, Sauerborn, Sauer et al (2005) and Glückler, Panitz and Wuttke (2015). The estimated values range between 1.0 (Spehl/Sauerborn/Sauer et al 2005) and 1.5 (Blume/Fromm 2000).…”
Section: Introductionmentioning
confidence: 99%
“…All studies indicated above have in common that they are either single case studies focusing on individual universities and the impact on their respective university locations (Blume/Fromm 2000;Hamm/Wenke 2002;Assenmacher/Leßmann/Wehrt 2004, Knappe 2006Leusing 2007;Pavel 2008;Mattes 2012;Hamm/Kopper 2016) or global studies considering the sum of universities in a federal state and the impact on the entire federal state in question (Glückler/Panitz/Wuttke 2015).…”
Section: Introductionmentioning
confidence: 99%